(untitled) (Revista Educação, Artes e Inclusão, 2024)
This article presents a set of reflections on the educational action entitled: Fundamental Rights and Contemporary Art: a multidisciplinary dialogue aimed at public high school students. The development of the creative process and knowledge about human rights enabled students to deepen their critical awareness of important issues arising from themselves and their collectivity. Their reports demonstrated aspects of the recognition and affirmation of themselves and their groups, in addition to the awareness of the symbolic violence to which they are subjected. The results denoted the achievement by students of a certain level of opposition to the barrier that impedes the exercise of citizenship provided for as the foundation of the Democratic Rule of Law in the Brazilian Federal Constitution/1988.